Clinical characteristics and outcome of patients over 60 years with Hodgkin lymphoma treated in Switzerland. Issue 2 (23rd December 2020) - Moccia, A. A.; Aeppli, S.; Güsewell, S.; Bargetzi, M.; Caspar, C.; Brülisauer, D.; Ebnöther, M.; Fehr, M.; Fischer, N.; Ghilardi, G.; Krasniqi, F.; Lang, N.; et al.
Abstract: Hodgkin lymphoma (HL) in older patients appears to be a different disease compared with younger patients with historically lower survival rates. This is related to a variety of factors, including increased treatment‐related toxicity, the presence of comorbidities, and biologic differences. In order to better assess the clinical characteristics, treatment strategies, and outcome of this particular population, we conducted a population‐based, retrospective analysis including 269 patients with HL older than 60 years (median age 71 years, range 60–94), treated between 2000 and 2017 in 15 referral centers across Switzerland. Primary endpoints were overall survival (OS), progression‐free survival (PFS), and cause‐specific survival (CSS). The vast majority of patients were treated with curative intent, either with a combined modality approach (chemotherapy followed by radiation therapy) or with systemic therapy. At a median follow‐up of 6.6 years (95% confidence interval [CI], 6.0–7.6), 5‐year PFS was 52.2% (95% CI, 46.0–59.2), 5‐year OS was 62.5% (95% CI, 56.4–69.2), and 5‐year CSS was 85.1.8% (95% CI, 80.3–90.1) for the entire cohort. A significant difference in terms of CSS was observed for patients older than 71 years in comparison to patients aged 60–70 years (hazard ratio 2.6, 1.3–5.0, p  = 0.005). Bleomycin‐induced lung toxicity (BLT) was documented in 26 patients (17.7%) out of the 147 patients exposed to this compound and was more frequent in patients older than 71 years (15/60, 25%). Outcome of HL pts older than 71 years appeared to decrease substantially in comparison to the younger counterpart. Treatment‐related toxicities appeared to be relevant, in particular, BLT. New, potentially less toxic strategies need to be investigated in prospective clinical trials in this particular frail population.